The American Effect on Physical Education and Sports in Turkey during the Early Republican Period - Sevda Korkmaz (Research in Social Sciences and Technology, 2022)
The establishment of the new Turkish state was accompanied by a new governmental system, modernization efforts, and reforms in all fields of life. Education, acknowledged as a phenomenon that prepares new generations for the future, became one of the main concerns among the republican reform programs. The lack of specialists to implement new educational programs required inviting professionals of the relevant fields from abroad, and the first to arrive was the American educational scientist John Dewey, only 9 months after the establishment of the republic. Thus, Turkish-American relations, which had begun with commercial and missionary activities during the Ottoman period, entered a new era. Dewey, who emphasized both mental and physical aspects of education as a whole, fostered the emergence of many new services in physical education and sports thanks to his reports. In addition to Dewey’s work, other American reports presented information and suggestions for physical education. The Young Men’s Christian Association (YMCA), which played an essential role in the spread of recreational sports activities, launched many new sports branches and endeavors. This study addresses the effects of those reports and American experts’ suggestions, observations, and approaches for physical education and sports in Turkey.